Frühe und späte HMPAO-SPECT während eines epileptischen Anfalls - Overbeck, Bettina; Grünwald, F.; Reinke, U.; Bockisch, A.; Gratz, K. F.; Biersack, H. J. (Nuklearmedizin - NuclearMedicine, 1990)
For presurgical evaluation of epilepsy a 44-year old patient with complexpartial seizures underwent HMPAO-SPECT. The morphology of the seizures, the MRI-scan, psychometry and ictal as well as interictal EEGs showed a left temporal origin of the seizures. Early images were obtained 20 min and late images 24 h following injection. On both scans a marked hyperperfusion was observed in the left temporal area. A crossed cerebellar diaschisis was also seen on both SPECTs. It could be shown that during ictal examinations there is no bloodflow-dependent wash-out from brain tissue.